Religion in the Conflict Flows - Syarif, Fajar (ADDIN, 2019)
This research analyzes the issue of religion in understanding multiple realities. So it needs to be explained how religion can be one of the triggers of the problem and eventually become tyrants of other religions or beliefs. The problem that is limited in this study is that it relates to religion which is limited to the reality of conflicts that occur, as long as the conflict is published; both through research and through mass media. Furthermore, this research tries to look at the background of the understanding of diversity that occurs in society, so that it can be explained how it exists in interreligious relations in order to be in line. Religious expression among religious followers can influence patterns of integration and conflict. It will increase and become a trigger for conflict when it relates to the factors of economic and political inequality both locally, nationally, and even the constellation that is originally reasonable in the community, then strengthens and becomes clear, especially in society so that conflicts arise. Social integration can be a conflict resolution if maintained through bonds among citizens and social organizations that cross primordial boundaries.